THE STATE OF THE ART IN RESEARCH INTO RURAL TOURISM IN SPAIN: AN ANALYSIS FROM THE PERSPECTIVE OF MARKETING - José Manuel Hernández-Mogollón; Ana María Campón-Cerro; Helena Maria Baptista-Alves (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 1970)
The study of rural tourism has been addressed from different perspectives, such as geography, sociology, psychology, economics, business management, tourism marketing, etc. This positions it as a multidisciplinary research field of great interest which is growing in strategic importance. However it requires appropriate tools to improve its performance and become more professional. The level of interest it now produces is palpable in the quantitative increase in the attention devoted to it in the scientific literature over recent years. Nevertheless there is a need to improve the quality of this research effort, especially in fields related to economics and the management of businesses and even more so with regard to issues related to marketing, all of which would contribute to a better understanding of issues such as the planning, management and marketing of these destinations and businesses. This paper is an analysis of rural tourism as an area of scientific research that aims to classify the most relevant topics in the field, with particular reference to those that focus on marketing and market research. Its main contribution is a proposal of a research agenda for the coming years.